(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The polyherbal formulation (PHF) containing different herbal extracts has been used to treat diabetic patients by Ayurvedic professionals in India. It has been well documented that the polyherbal plant extracts more productively diminish the elevated blood glucose level as compared with the single plant extract. Methodology: The PHF contains the concentrated extracts of Syzygium cumini, Annona squamosa, Momordica charantia, Tinospora cordifolia, Gymnema sylvestre, and Curcuma longa. The present study reports the impact of PHF alone and with metformin on various preclinical models of hyperglycemia. Results: PHF treatment with alone and in combination with metformin evoked a noteworthy antihyperglycemic impact on glucose loaded (P < 0.05), epinephrine-induced hyperglycemia (P < 0.05), and alloxan-induced diabetic rats (P < 0.05). PHF treatment also modifies glucose tolerance curve pattern both in normal and in diabetic rats. The treatment with polyherbal formulation was significantly improved architecture of Î²-islets of Langerhans as compared with the diabetic rats. The PHF significantly decreased (P < 0.05) triglyceride, cholesterol, and high-density lipoprotein as compared to diabetic control group. The dynamic phytoconstituents present in this PHF are flavonoids, phenolic compound, triterpene saponins like gymnemic acids, and gymnemasaponins advance the arrival of insulin and postpone the assimilation of glucose. Conclusion: PHF treatment in combination with metformin is found to be useful in the management of preclinically induced diabetes mellitus.